Lysine-selective molecular tweezers are cell penetrant and concentrate in lysosomes - Zizheng Li (Nature Portfolio, 2021)
Li et al. design and synthesize fluorescently labeled molecular tweezers to explore their internalization, intracellular localization, and mechanism of endocytosis in brain cells including neurons and astrocytes. The authors find that MTs are internalized in neurons and astrocytes, at least partially through dynamin-dependent endocytosis, and concentrate rapidly in acidic compartments, primarily lysosomes.